Analisis Pemilihan Warna Pada Industri Produk Kubah Putra Jamin Padangpanjang - Aryadi, Mirda (INSTITUT SENI INDONESIA PADANGPANJANG, 2023)
AbstractIndustrial designs in the field of dome architecture have long-term potential to become sustainable projects. The choice of color is an element of art that cannot be separated from the architectural design of the dome wherever this product is applied. The research